Pochodzenie rodu Branickich herbu Gryf. Pogląd historyka ustroju i prawa - Tomasz Kruszewski (Wrocławsko-Lwowskie Zeszyty Prawnicze)
The author redefines the subject of origins of the magnate House of Branicki (Gryf) due to the despicable manner in which his views were criticized. Ultimately, he argues that the origins of the House of Branicki are more likely to be descendants from Pomeranian Dukes through the House of Griffin.